Psychosocial and sociodemographic factors associated with gestational blood glucose levels in women attending public hospitals: Results from baseline of MAASTHI cohort. - Prafulla Shriyan; Srinidhi Koya; Eunice Lobo; Onno Cp van Schayck; Giridhara R Babu (PLoS ONE)
Background Understanding psychosocial environment is important for improving maternal and fetal health outcomes during pregnancy. We aimed to identify the association between gestational blood glucose levels and psychosocial and demographic factors in pregnant women. Methods In the MAASTHI pregnancy cohort in Bengaluru, we assessed depressive symptoms, and social support using validated scales at baseline in first trimester. A 2-hour 75 g oral glucose tolerance test (OGTT) was administered between 24-36 weeks of gestation. We examined the relation between psychosocial factors assessed at baseline and gestational blood glucose levels in second/third trimester using multivariate linear regression and explored association between serum cortisol and gestational blood glucose levels in subgroup samples. Results We found that 9% of pregnant women had depressive symptoms and 14.3% had Gestational Diabetes Mellitus (GDM). Psychosocial factors, including depressive symptoms, have a significant correlation with gestational fasting(β = 0.12, p-value<0.05) and postprandial blood sugar level(β = 0.23, p-value<0.05) and poor social support were found to have a significant association with gestational fasting blood glucose levels(β = 1.45, p-value <0.05) and postprandial blood sugar levels(β = 2.60, p-value <0.05). The sociodemographic factors such as respondent education, occupation, social and economic status were associated with gestational blood sugar after adjusting for potential confounder variables. Conclusion Depressive symptoms and poor social support earlier in pregnancy were significantly associated with increased gestational blood glucose levels. Early detection and recognition of modifiable psychosocial risk factors can reduce glucose intolerance during pregnancy. Evaluating the benefits of screening for psychosocial factors and timely management of gestational diabetes mellitus can be helpful in India.